Spatial reference points for groundfish. (27th July 2016) - Reuchlin-Hugenholtz, Emilie; Shackell, Nancy L.; Hutchings, Jeffrey A.; ,
Abstract: According to density-dependent habitat selection theory, areas of high density can be indicative of high population productivity and have positive individual fitness consequences. Here, we explore six groundfish populations on the Scotian Shelf, Canada, where a decline in areas of high density beyond a certain threshold is associated with disproportionately large declines in Spawning Stock Biomass (SSB). This is evidenced by empirical, concave, positive relationships between high-density areas (HDAs) and SSB. We introduce a methodology to estimate the threshold below which SSB declines increasingly faster per unit of HDA decline. The spatial threshold among these six stocks was remarkably consistent; when stocks lose 70–80% of HDAs, disproportionately large SSB declines are likely to occur. We propose that spatial thresholds could serve as spatial reference points to complement existing SSB limit reference points (LRPs). For some stocks we identify spatial thresholds which correspond to SSB levels that exceed those associated with the designated SSB LRP, suggesting that a review of these SSB LRPs warrants merit. For other stocks, spatial reference points can be used in concert with SSB reference points, strengthening efforts to incorporate a precautionary approach to fisheries management. Our results warrant further research into the general application of HDA as spatial limit and target reference points for fisheries management in addition to other population status indicators within a broad recovery framework.